Utilização do consumo máximo de oxigênio e do limiar de lactato como preditores do desempenho de corredores amadores em corridas de 5km e meia maratona - Eliney Silva Melo (2011)
This study investigated the use of maximum oxygen uptake (VO2max) and lactate threshold (LT) identified by the method of individual anaerobic threshold (IAT) as predictors of 5 km and 21.1 km (half marathon) race performance. Twelve men, amateur runners, volunteered to take part in the study. VO2max was determined using an incremental protocol on a treadmill and the LT was determined using the IAT method adapted to running track. All subjects participated in two official races, one of 5 km and 21.1km (half marathon), and the average running speed was calculated. We found a high correlation (r = 0.81, p = 0.001) between LT and the average speed of 5 km, and a moderate correlation between LT and the half marathon (r = 0.57, p = 0.054). The correlations between VO2max and average speeds of 5km and half marathon were, respectively, (r = 0.45, p = 0.143 and r = 0.32, p = 0.319). The results suggests that the LT is a good predictor of amateur runners 5km performance but not of half marathon performance, and that the VO2max was unable to predict the performance of amateur runners in 5km and half marathon events